Avoiding coupling fluid-sample interaction in confocal Raman depth s profiling with immersion objectives - Tomba, Juan Pablo (2008)
A strategy based on the use of a protective coating as a separating medium to prevent sample-coupling fluid direct contact when one performs depth profiling by Confocal Raman microspectroscopy (CRM) with immersion objectives was reported. A simple device with aluminum frame for reversible application of protective coating was designed. The polyethylene (PE) film was cut from the original sheet to perfectly fit in the dimensions of the frame. The air between the film was evacuated through a channel formed in the main frame, to promote good physical contact between these elements. A rubber gasket, with a cut at the point of air evacuation, was placed between frame and sample to prevent air entrance. The response of the PP test film is found at higher depths and produces a thickness of 42μm. It was also observed that the broadening of all the planar interfaces found is similar, indicating that depth resolution remains constant with focusing depth.